Comparative analysis of various compensating devices in energy trading radial distribution system for voltage regulation and loss mitigation using Blockchain technology and Bat Algorithm. (November 2021) - Yuvaraj, T.; Devabalaji, K.R.; Srinivasan, S.; Prabaharan, Natarajan; Hariharan, R.; Haes Alhelou, Hassan; Ashokkumar, B.
Abstract: The electric power distribution plays a crucial part in the power systems to maintain the power quality and stability of the system for loss mitigation and voltage regulation. The reactive power compensators like a capacitor, DG, and DSTATCOM play a vital role in power quality and stability improvement by providing proper reactive power in the distribution system. This article provides a critical review and comparative analysis of various compensating devices allocation to achieve power loss mitigation and voltage regulation in the radial distribution system (RDS). The Bat Algorithm (BA) and Voltage Stability Index (VSI) are utilized for determining the optimal size and site of the compensating devices in the RDS. Further, the application of Blockchain technology is utilized for voltage regulation of energy trading RDS. To show the effectiveness of the present study, an IEEE 33 test system is considered. All three compensators are implemented in IEEE 33 test system and compared with existing approaches. The present study is very much helpful to the Distribution Network Operators for selecting the suitable compensator in real-time applications.